KEWAJIBAN SEORANG MUKMIN MELUNASI HUTANG: STUDI MA`ANI ALHADITH - Eko Rahmanto (UIN Raden Mas Said Surakarta, 2016)
Hadith has been known as the second source of Islamic law after Qur’an. To understand its meaning properly, a comprehensive approach is required. Textual understanding will only make Hadith cannot be applied according to its context. For instance, Hadith about the Muslim’s soul after passing away will be detained because of his/her debts. To understand this Hadith, not only linguistic approach is required but also sociological approach so that the meaning of this Hadith could be understood correctly, and applicable in the societal life. Through the study of Ma’ani Alhadith, it is found that debt, which is not yet paid, does not merely become a burden to one who has died, but also person who is still living. It is related to someone’s respectability, reputation, and also his or her life in the society. Therefore, if someone has passed away and leaving unpaid debt, his/her heirs are obliged to pay it.